Vascular Injury in Carpal Tunnel Surgery: Evaluating the Impact of Scalpel versus Scissors in Flexor Retinaculum Release (Medical Forum Monthly, 2026)
Objective: To evaluate the frequency of vascular injuries in patients undergoing carpal tunnel release (CTR), with a specific comparison between scalpel and scissors techniques for flexor retinaculum division, and to assess the association with demographic and clinical variables.Study Design: Cross sectional study.Place and Duration of Study: This study was conducted at the emergency wards of DHQ Teaching Hospital and Mufti Mehmood Memorial Teaching Hospital from January 2024 to January 2025.Methods: A total of 290 patients who underwent CTR were retrospectively analyzed. Patients with clinically diagnosed carpal tunnel syndrome (CTS), confirmed by nerve conduction studies (NCS) and/or electromyography(EMG), were included. Exclusion criteria comprised incomplete surgical records, previous CTR, concomitant hand surgeries, and preexisting vascular disorders unrelated to CTS. Patients were categorized based on the surgical instrument used for flexor retinaculum release (scalpel vs. scissors). The relationship between vascular injuries and patient age, gender, symptom duration, and severity was assessed. Statistical analysis was performed using SPSS version 26.0.Results: Among the 290 patients, the overall incidence of vascular injury was 11.7%. A significantly higher rate of vascular injury was observed in the scissors group (25.6%) compared to the scalpel group (5.5%) (p < 0.05). Nostatistically significant association was found between vascular injuries and demographic variables (age, gender) or clinical characteristics (symptom duration and severity).Conclusion: The findings demonstrate a significant difference in safety profiles between surgical techniques for CTR. The use of scissors for flexor retinaculum division is associated with a markedly higher risk of vascular injury compared to the scalpel technique, suggesting that instrument choice is a critical factor in minimizing intraoperative complications.